Many P-element insertions affect wing shape in Drosophila melanogaster. - Weber, K.; Johnson, N.; Champlin, D.; Patty, A. (Genetics, 2005)
A screen of random, autosomal, homozygous-viable P-element insertions in D. melanogaster found small effects on wing shape in 11 of 50 lines. The effects were due to single insertions and remained stable and significant for over 5 years, in repeated, high-resolution measurements. All 11 insertions were within or near protein-coding transcription units, none of which were previously known to affect wing shape. Many sites in the genome can affect wing shape.